Consequences of Cultural and Behavioral Difference of Tourist: Study of Australian and Indonesian Tourist Who Visit Lombok Island, West Nusa Tenggara - Rinuastuti, Baiq Handayani (Graduate School, Universitas Brawijaya, 2015)
This study aims at identifying behavior differences of Australian tourists and domestic tourists who visit Lombok island, and determining as well as analyzing the Hofstede cultural variables (power distance, individualistic-collectivist, uncertainty avoidance, masculine-feminine, long-term orientation) that may explain the differences in behavioral intention (to have activities, to interact, and to transact) of Australian and domestic tourists. This study was conducted on 160 Australian and domestic tourists who were visiting the island. Sampling was done by convenience sampling. Methods of data analysis were conducted by using t-test and discriminant analysis. The results of this study showed that there are differences in behavioral intentions of Australian travelers and the domestic ones in having activities, interacting, and transacting, and these differences can be explained by the cultural background of the tourists that are based on cultural orientation at the individual level. This study extends the use of CVSCALE and may be considered as an addition to the use of secondary data in determining the value of culture, as well as providing clearer framework on the limits of the relationship of cultural values and the various tourist behaviors. Keywords: Individualist-Collectivists, Longterm orientation, Masculine-feminine, Power distance, Tourist behavior, Uncertainty avoidance